2012
DOI: 10.1371/journal.pone.0032034
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Expression and Systems Biology Analysis of Bovine Monocyte-Derived Macrophages in Response to In Vitro Challenge with Mycobacterium bovis

Abstract: Background Mycobacterium bovis, the causative agent of bovine tuberculosis, is a major cause of mortality in global cattle populations. Macrophages are among the first cell types to encounter M. bovis following exposure and the response elicited by these cells is pivotal in determining the outcome of infection. Here, a functional genomics approach was undertaken to investigate global gene expression profiles in bovine monocyte-derived macrophages (MDM) purified from seven age-matched non-related females, in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 89 publications
7
56
1
Order By: Relevance
“…Of the 16,793 total genes presented on the chips, 2269 genes have false discovery rate (FDR) ≤0.01, p < 0.01, and fold change >2, in which we found that 1103 (2184 probes) were upregulated and 1166 (2318 probes) were downregulated. With such stringent criteria, M. bovis challenge was found to cause significant fold changes in thousands of genes, which might be attributed to the fact that the MOI used in this study was higher than that used by other researchers (MOI, 10 vs. 2) (Magee et al, 2012). CSF3, CCL20, and CSF2 were the top upregulated genes (+11.47, +11.04, and +9.81 in log 2, respectively; Table 1), whereas killer cell lectin-like receptor-like (LOC618591), RAS guanyl releasing protein 3 (calcium and DAG-regulated) (RASGRP3), and solute carrier family 1 (glial high affinity glutamate transporter), member 3 (SLC1A3) were the top downregulated genes (−7.14,−6.03, and −6.01 in log 2, respectively; A recent study by Magee et al (2012) addressed the same question using M. bovis at an MOI of 2 to challenge bovine MDMs and studied transcription at 6 h post infection.…”
Section: Gene Expression Profilesmentioning
confidence: 72%
See 2 more Smart Citations
“…Of the 16,793 total genes presented on the chips, 2269 genes have false discovery rate (FDR) ≤0.01, p < 0.01, and fold change >2, in which we found that 1103 (2184 probes) were upregulated and 1166 (2318 probes) were downregulated. With such stringent criteria, M. bovis challenge was found to cause significant fold changes in thousands of genes, which might be attributed to the fact that the MOI used in this study was higher than that used by other researchers (MOI, 10 vs. 2) (Magee et al, 2012). CSF3, CCL20, and CSF2 were the top upregulated genes (+11.47, +11.04, and +9.81 in log 2, respectively; Table 1), whereas killer cell lectin-like receptor-like (LOC618591), RAS guanyl releasing protein 3 (calcium and DAG-regulated) (RASGRP3), and solute carrier family 1 (glial high affinity glutamate transporter), member 3 (SLC1A3) were the top downregulated genes (−7.14,−6.03, and −6.01 in log 2, respectively; A recent study by Magee et al (2012) addressed the same question using M. bovis at an MOI of 2 to challenge bovine MDMs and studied transcription at 6 h post infection.…”
Section: Gene Expression Profilesmentioning
confidence: 72%
“…Pathway analysis using different databases produced significant redundancy and unrelated functions; although this may simply be due to the large number of possible pathways, it is more likely that M. bovis challenge may lead to changes that are much more complicated than inflammatory responses and apoptosis. For example, activation of the RIG-I-like receptor pathway (23th) by viral RNA was shown previously (Magee et al, 2012). Intracellular Legionella pneumophila interact with RIG-I-like receptors (Monroe et al, 2009), as well; thus, it is possible that M. bovis also activates this pathway.…”
Section: Pathway Analysis Of In Vitro Challengementioning
confidence: 86%
See 1 more Smart Citation
“…2); another important category (37%) included the genes involved in metabolic processes and ion transport. Also Meade et al (2007), Magee et al (2012) and Nalpas et al (2013) have performed gene expression screenings, with DNA microarrays containing immunity genes, on peripheral blood mononuclear cells from non-infected versus M. bovisinfected cattle. Meade et al (2007) reported the lower relative expression of key innate immune genes in the infected animals.…”
Section: Discussionmentioning
confidence: 99%
“…Meade et al (2007) reported the lower relative expression of key innate immune genes in the infected animals. Magee et al (2012) revealed a differential expression for genes involved in: (1) the inflammatory response; (2) cell signalling pathways, including TLR and intracellular pathogen recognition receptors; and (3) apoptosis. Nalpas et al (2013) demonstrated the differential expression of immune, apoptotic and cell signalling genes in the non-infected versus infected animals.…”
Section: Discussionmentioning
confidence: 99%